2017
DOI: 10.1001/jamainternmed.2016.9627
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reminder Devices on Medication Adherence

Abstract: IMPORTANCEForgetfulness is a major contributor to nonadherence to chronic disease medications and could be addressed with medication reminder devices.OBJECTIVE To compare the effect of 3 low-cost reminder devices on medication adherence.DESIGN, SETTING, AND PARTICIPANTS This 4-arm, block-randomized clinical trial involved 53 480 enrollees of CVS Caremark, a pharmacy benefit manager, across the United States. Eligible participants were aged 18 to 64 years and taking 1 to 3 oral medications for long-term use. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
140
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(147 citation statements)
references
References 24 publications
(38 reference statements)
3
140
1
3
Order By: Relevance
“…Further, there was no significant difference in the improvement in adherence whether the intervention was simple or complex (two or more components) 38. The reviewers concluded that ‘simple one-component interventions might be a promising way to improve medication adherence in a CHD population, as they would be easier to replicate in different settings and on a large scale.’38 However, recent trials that have assessed alternatives to polypill-based care (reminder devices either alone39 or in combination with financial incentives and social support40) have found no statistically significant difference in adherence to usual care.…”
Section: Discussionmentioning
confidence: 99%
“…Further, there was no significant difference in the improvement in adherence whether the intervention was simple or complex (two or more components) 38. The reviewers concluded that ‘simple one-component interventions might be a promising way to improve medication adherence in a CHD population, as they would be easier to replicate in different settings and on a large scale.’38 However, recent trials that have assessed alternatives to polypill-based care (reminder devices either alone39 or in combination with financial incentives and social support40) have found no statistically significant difference in adherence to usual care.…”
Section: Discussionmentioning
confidence: 99%
“…Other monitoring devices include mobile device medication reminders, smart pillboxes that track vial openings, and ingestible pill biosensors (Checchi et al, 2014). The clinical benefit of these devices for improving long-term compliance is still lacking (Choudhry et al, 2017). Systematic collection of treatment compliance data, health status, and patient outcomes are needed to determine which treatments and patient compliance strategies provide maximal clinical benefit.…”
Section: High Precision Treatmentmentioning
confidence: 99%
“…In contrast, a randomised controlled trial of more than 53 000 patients aged 18-66 who were taking three medications or fewer and using one of three reminder devices did not show any evidence of improved adherence compared with controls 16. These findings may not be transferable to the older cohort, who often use multi-compartment MCAs for polypharmacy in the UK.…”
Section: What Is the Evidence For The Use Of Multi-compartment Mcas?mentioning
confidence: 70%